A ring vibration isolator enhanced by a nonlinear energy sink. (15th September 2021) - Tan, Dong-Dong; Lu, Ze-Qi; Gu, Dong-Hao; Ding, Hu; Chen, Li-Qun
Abstract: Using a nonlinear energy sink to reduce vibration in a broad frequency range has been widely discussed. This paper reports on a study of nonlinear damping of vibration in a system consisting of a ring isolator (under harmonic excitation) and a nonlinear energy sink, with the goal of designing a broadband isolator of light weight. A full mathematical model of the ring with the nonlinear energy sink is established, leading to two coupled nonlinear partial differential equations (PDEs) with closed boundary conditions. The PDEs are discretized via the Galerkin method. A harmonic balance analysis is used to derive the frequency response functions of the transmissibility, and the harmonic balance solutions are compared with numerical results using a finite difference method. It is found that the disappearance of a crossed frequency response curve may decrease the transmissibility at the resonances. Also, the quasi-periodic motion can indicate emergence of a knot-shaped crossed resonance curve. The effects of mass, nonlinear stiffness, and damping ratio are examined. With a suitable ring size, the nonlinear energy sink in a ring isolator is superior to a conventional linear absorber of the same mass, damping, and stiffness.